Raising Ducks Using Feed Supplementedwith Tea Dregs in Karang Taruna “Tunas Harum-2” Kaliputih Village, Purwojati Municipality, Banyumas - Elly Tugiyanti; Sigit Mugiyono; Ibnu Hari Sulistyawan (Universitas Mathla'ul Anwar Banten, 2021)
Rice field constitutes 70 percent of Kaliputih village in Purwojati municipality, Banyumas and half of the community are farmers. İt motivated the community and Karang Taruna 'Tunas Harum -2' to raise ducks, but they faced some issues of obtaining DOD and high mortality of ducks. Therefore, it required some innovation to solve the problems, namely artificial insemination, hatching eggs in an incubator, feed processing by utilizing the available agricultural waste, and incorporating antioxidants from waste, tea dregs. Tugiyanti et al. (2019) reported that fermented tea dreg contains high antioxidants that could improve duck health and the quality of duck eggs and meat. This community service engaged an extension/technology adoption program through seminars, practice/demo, evaluation as well as training for instructors. The materials (theory and practice) designed for the members of Karang Taruna included the method of duck farming, artificial insemination for ducks, tea dreg fermentation, methods for feed formulation, and incorporating 3% tea dreg to the feed and practice hatching eggs in an incubator. The participants, including the village government officials and the community, had successfully partaken in the process of technology transfer and practice. Conclusively, the community service program can modify the community habit in duck farming and solve issues regarding DOD, feed, and production.